Analisis Faktor-Faktor Yang Mempengaruhi Financial Distress - Nadira Alisha Putri; Sucahyo Heriningsih (Jurnal Akuntansi dan Keuangan Daerah, 2023)
Financial distress is a condition of decline in the company's performance and finances that can have an impact on the company's bankruptcy. Financial distress needs to be overcome early so that the company avoids bankruptcy. Therefore, it is necessary to analyze financial distress to anticipate bankruptcy. The study was conducted with the aim of examining the effect of operating cash flow, leverage, operating capacity, and company size on financial distress. The type of research conducted is quantitative research with purposive sampling methods. The data used is secondary data with financial statements from real estate and property sub-sector companies for the 2019-2021 period listed on the Indonesia Stock Exchange (IDX). Companies that became a sample of 61 companies in 3 periods with a total sample of 183 samples. The method used in the study was multiple linear regression analysis using the SPSS program version 25. The results showed that operating cash flow and leverage affect financial distress. Variables that do not affect financial distress in this study are operating capacity and company size.